Better livelihoods through poultry enterprises - Gaurav, Pratyush (Technical Centre for Agricultural and Rural Cooperation, 2018)
In the state of Bihar, India, the Integrated Poultry Development Programme has been working to improve the livelihoods of poor and marginalised rural people. By working to strengthen the entire value chain, the project has increased the income of the most marginalised groups, improved their nutritional diversity, and provided livelihoods for input suppliers and dedicated community professionals who support farmers and facilitate market linkages.